Strategy of Surgical Correction of Postcoarctation Thoracic Aortic Aneurysms - Kravchenko, Vitalii I.; Tarasenko, Yurii M.; Derkach, Alla V.; Kravchenko, Ivan M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the experience of surgical treatment of postcoarctation aneurysms and to propose an optimal strategy in choosing a correction method. Materials and methods. An analysis of 91 cases of postcoarctation aneurysm over a 25-year period was carried out. Eighty-five people (93.4%) were operated on, 6 patients (6.6%) were not operated on for various reasons. The patients were divided into clinical groups depending on the method: group I included 69 patients (75.8%) who underwent open correction of postcoarctation aneurysm. Group II consisted of 16 patients (17.6%) after endovascular or hybrid treatment. Results. The obtained results demonstrated significant achievements and pronounced clinical effect of the performed surgical correction of postcoarctation aneurysms. We identified indications and contraindications for the correction of postcoarctation aneurysms by various methods: open, endovascular, and hybrid. It was found that the advantages of the endovascular technique are: minimally invasive approach, absence of a large surgical wound, shorter duration of the operation, faster activation of the patient after the intervention, shorter length of hospital stay in the postoperative period, faster return to a full active life. When studying the long-term results, based on the SF-36 questionnaire scores, it was established that the quality of life was higher among patients who underwent endovascular and hybrid correction of postcoarctation aneurysms. Conclusion. Clear indications for surgical correction of postcoarctation aneurysm and the choice between open surgery, endovascular or hybrid intervention should be determined based on detailed analysis and with the participation of the entire heart team with mandatory consideration of: patient age, comorbidities, expected duration and quality of life of each patient after surgery.